Catalytic asymmetric tandem Friedel–Crafts alkylation/Michael addition reaction for the synthesis of highly functionalized chromans - Peng, Jiahuan; Du, Da-Ming (Beilstein Journal of Organic Chemistry, 2013)
The enantioselective tandem Friedel–Crafts alkylation/Michael addition reaction of indoles with nitroolefin enoates catalyzed by a diphenylamine-linked bis(oxazoline)-Zn(OTf)2 complex was investigated. This tandem reaction afforded functionalized chiral chromans in good yields with moderate to high stereoselectivities (up to 95:5 dr, up to 99% ee).
Keywords: asymmetric catalysis; bis(oxazoline); chroman; Friedel–Crafts alkylation; tandem reaction